Size-segregated analysis of PAHs in Urban air: Source apportionment and health risk assessment in an Urban canal-adjacent environment - Siwatt Pongpiachan; Danai Tipmanee; Chukkapong Khumsup; Phoosak Hirunyatrakul; Muhammad Zaffar Hashmi; Saran Poshyachinda (PLoS ONE, 2025)
This study examines the distribution, origins, and health hazards of polycyclic aromatic hydrocarbons (PAHs) across six particle size fractions obtained from an urban rooftop location in Bangkok, Thailand. We collected PM samples using a six-stage cascade impactor at a canal boat port, trapping PAHs in particle sizes ranging from ultrafine (PM0.65–1.1) to coarse (PM7.0 and beyond) over an 11-week period. We utilized gas chromatography-mass spectrometry to quantify twelve PAH congeners. Results indicated that PAHs primarily concentrate in fine particles (PM2.1–3.3), with traffic emissions from gasoline and gasoline cars being the principal sources, augmented by emissions from diesel canal boats and industrial activities. The health risk assessment showed that the lifetime lung cancer risk (LLCR) values for all particle sizes were less than 1×10−6. This means that PAH exposure in this area has a very low cancer risk. Principal Component Analysis (PCA) and Positive Matrix Factorization (PMF) found traffic and industrial emissions as the primary sources of PAHs, with canal boats accounting for 5% of the total. These findings highlight the necessity of specific emission control regulations and advocate for the implementation of cleaner fuel alternatives and electric propulsion in canal transit to enhance urban air quality in Bangkok.